Teaching Speaking By Using Media Audiovisual - Septiana Wandira; Dwi Nur hadiansyah (JOEY: Journal of English Ibrahimy, 2022)
students can be classified as smart if they are good at speaking English Many studies have been carried out to improve students' speaking skills and still do not get promising results. In this study, the researcher will try to teach speaking by using media audiovisual. there is an effect of audiovisual on speaking ability from the calculation of the mean of the pre-test and The post-test which shows a change in the calculation of the mean pre-test value and post-test value the interval point in the pre-test table is 60-67 or 32% of the student in the class and the post-test table, the interval score is 85-87 with 28% of students in the class. It shows the improvement in the score of the student. So the treatment can improve the student's understanding in the class. in questioner also show a positive response from the student that answer mostly satisfying answers to all questions.